Investigation of metabolic bone disease by in vivo neutron activation analysis - Eastell, Richard (The University of Edinburgh, 1984)
A technique for measuring total body calcium (TBCa) by in vivo neutron activation analysis (IVNAA) was described. It had a precision of 1.8% for a dose of 13 mSv. TBCa was measured in 40 healthy volunteers and the mean value (SD) for 20 men was 1143g (134g) and for 20 wcmen it was 821 g (124g). A formula for predicting TBCa (TBCap) from height in men and from span and years postmenopause in wcmen was derived. The results from patient groups were expressed as a ratio of TBCa to TBCap, the calcium ratio (CaR). The mean CaR in eight wcmen with wrist fracture was 1.00 (0.10, SD) and in 14 wcmen with vertebral fractures was 0.87 (0.06, SD). The latter group had a significantly lower CaR than the female controls of 1 .00 (0.07, SD, P<0.001). The TBCa was normalized for span alone to obtain an index reflecting the bone lost since the menopause, the osteopaenia index. Patients with vertebral fractures all had values below 0.78 and so this was considered the fracture threshold. A low mean value for CaR was found in 14 patients with primary hyperparathyroidism. Significant increases in TBCa were found in four out of seven patients followed for up to 34 months postoperatively. The initial mean CaR was 0.85 (P<0.001 ). Seven wcmen with osteomalacia due to malabsorption had a low mean TBCa and osteopaenia index (P<0.001). One patient who was remeasured after eight months of vitamin D therapy had an 18% increase in TBCa, the largest increase found in any patient in the present study. Twelve patients were measured prior to, or shortly after, renal transplantation. The eight men had a mean CaR of 0.93 (P<0.05) and the four wcmen a mean value of 0.82. There was no significant change following renal transplantation over an average of 17 months. This result was attributed to a balance between the healing of renal osteodystrophy and the osteopaenic effect of steroid therapy. Forty-one men studied after peptic ulcer surgery had a low mean CaR of 0.94 (0.07, SD, P<0.01 ). The reduction in bone mass was similar for patients after partial gastrectomy and for those after vagotomy and drainage procedures. The hypothesis was proposed that bone disease after peptic ulcer surgery was due to secondary hyperparathyroidism caused by calcium malabsorption and not by subclinical osteomalacia. This was supported by the following findings. Plasma 25-hydroxycalciferol was normal when compared with season-matched controls. However, there were low plasma calcium and high parathyroid hormone levels compared with age-matched controls. Dietary calcium was normal but 7-day calcium retention was increased when the calcium was given as a solution.